The Effect of Coconut Oil and Hibiscus Rosasinensis on Ration Degradability and Number of Protozoa - Suparwi, Suparwi (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2000)
Concentrated diet based on rice bran 69%, coconut meal 30%, urea 1% and field grass (fg), parsial defaunation agent Hibiscus rosasinensis (Hr) and coconut oil (Co) was used in propotion 37,5% fg + 2,5% Hr; 35% fg + 5% Hr; 37,5% fg + 2,5% Co and 35% + 5% Co. the feed of concentrate and feed grass 60 : 40 % are evaluated in vitro for dry matter degradability (DMD), organic matter degradability (OMD) and number of protozoa (NP). Variance analysis and orthogonal contrast was applied according to Steel and Torrie (1981). The result show that defaunation agent Hr and Co 2,5% and 5% increased (P< 0.01) DMD in the order 60.20; 59.40; 56.60 and 55.60 respectively, compare with no defaunation agent (54,60%). It also increased OMD 62.20%; 60.40; 58.40 and 57.20% compare with no agent (56.40%). While number of protozoa decreased (P< 0.01) 2.456; 2.316; 2.396 and 2.286 x 104/ml rumen liquid compare with no defaunation agent (2.564 x 104/ml rumen liquid). (Animal Production 2(2): 53-59 (2000)Â Key words : Hibiscus rosasinensis, digestibility, and number of protozoa